Efficacy and toxicity of sorafenib in the treatment of advanced medullary thyroid carcinoma: A systematic review and meta‐analysis. Issue 8 (4th June 2019) - Vuong, Huy Gia; Ho, An Thi Nhat; Tran, Thao T. K.; Capdevila, Jaume; Benekli, Mustafa; Nakazawa, Tadao; Katoh, Ryohei; Kondo, Tetsuo
Abstract: Introduction: The aim of this study is to investigate and summarize the treatment efficacy and adverse effects (AEs) of sorafenib in the treatment of metastatic medullary thyroid carcinomas (MTCs). Methods: We included studies reporting the treatment efficacy or drug toxicity of sorafenib as a single therapeutic agent in MTCs. Pooled incidence and its 95% confidence interval (CI) for complete response, partial response (PR), stable disease (SD), and sorafenib‐related AEs were calculated using random‐effect model. Results: Eight trials with 101 metastatic MTCs were included for meta‐analyses. The overall PR and SD were 21% (95% CI = 9‐33) and 58% (95% CI = 41‐75), respectively. Hand‐foot syndrome, diarrhea, alopecia, mucositis, skin rash, fatigue, and hypertension were the most commonly observed AEs. Conclusion: Our results show that sorafenib treatment has a modest effect and might be a candidate treatment in patients with metastatic MTCs who have failed other therapeutic regimens.